2006
DOI: 10.4315/0362-028x-69.8.1808
|View full text |Cite
|
Sign up to set email alerts
|

Treatments Using Hot Water Instead of Lactic Acid Reduce Levels of Aerobic Bacteria and Enterobacteriaceae and Reduce the Prevalence of Escherichia coli O157:H7 on Preevisceration Beef Carcasses

Abstract: Lactic acid has become the most commonly used organic acid for treatment of postevisceration beef carcasses. Many processors have also implemented 2% lactic acid washes on preevisceration carcasses. We previously demonstrated that hot water washing and steam vacuuming are effective carcass interventions. Because of the effectiveness of hot water, we compared its use with that of lactic acid as a preevisceration wash in a commercial setting. A commercial hot water carcass wash cabinet applying 74ЊC (165ЊF) wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 26 publications
3
42
0
Order By: Relevance
“…It can also prevent oxidative degradation in meat based products (Bosilevac et al 2006) and can be used as antimicrobial agent for surface decontamination of carcasses (USDA-FSIS 2010). A study conducted by Harris et al (2006) in which they sprayed 2.0-4.0 % lactic acid solution on beef surfaces and delineated that E. coli O157:H7 and Salmonella population were significantly decreased up to 1.5 to 2.0 logs.…”
Section: Organic Acids As Antimicrobial Agentmentioning
confidence: 99%
“…It can also prevent oxidative degradation in meat based products (Bosilevac et al 2006) and can be used as antimicrobial agent for surface decontamination of carcasses (USDA-FSIS 2010). A study conducted by Harris et al (2006) in which they sprayed 2.0-4.0 % lactic acid solution on beef surfaces and delineated that E. coli O157:H7 and Salmonella population were significantly decreased up to 1.5 to 2.0 logs.…”
Section: Organic Acids As Antimicrobial Agentmentioning
confidence: 99%
“…However, the reduction rates reported were found to be dependent of experimental factors such as the temperature, pressure and the duration of the treatment (Loretz et al, 2011). The effectiveness of carcass decontamination by hot water was demonstrated by Bosilevac et al (2006). These authors conducted a study in a commercial abattoir and reported 2.7 log reductions in both aerobic plate counts and Enterobacteriaceae counts on pre-evisceration bovine carcasses washed in a cabinet with water at 74°C for 5.5 seconds.…”
Section: Carcass Decontamination Treatmentsmentioning
confidence: 99%
“…In a study by Barboza de Martinez et al (2002) spraying carcasses at the end of slaughter by lactic acid (1.5%) yielded reductions of 0.5, 1.8 and 0.6 logs, respectively, for aerobic bacteria, coliforms and E. coli. In another study, lactic acid (2%; 42°C) spraying of pre-eviscerated bovine carcasses was reported to reduce the prevalence of E. coli O157:H7 by 35% as well as aerobic bacteria and Enterobacteriaceae counts by respectively 1.6 and 1.0 logs (Bosilevac et al, 2006). Other chemicals such as chlorine, trisodium phosphate, acidified sodium chlorite and peroxyacids are also used for meat decontamination but to a lesser extent.…”
Section: Carcass Decontamination Treatmentsmentioning
confidence: 99%
“…Practices to prevent or reduce E. coli O157:H7 contamination of beef carcasses are primarily applied at the processing level, with the most common treatments being hide washes, trimming of contaminated carcass parts, steam vacuuming, hot water and acid washes, and steam treatment (1,2,4,5). Despite the implementation of these practices, there continue to be significant numbers of recalls and beef-linked illness caused by this pathogen.…”
mentioning
confidence: 99%